2008
DOI: 10.1681/asn.2007121386
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Growth Hormone is Cardioprotective in Uremia

Abstract: Growth hormone (GH) is required to maintain normal cardiac structure and function and has a positive effect on cardiac remodeling in experimental and possibly human disease. Cardiac resistance to GH develops in the uremic state, perhaps predisposing to the characteristic cardiomyopathy associated with uremia. It was hypothesized that administration of low-dosage GH may have a salutary effect on the cardiac remodeling process in uremia, but because high levels of GH have adverse cardiac effects, administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…These results suggest that administration of GH may prevent hHcys-induced glomerular injury and therefore the maintenance of normal GH level may be important for the protection of kidneys from hHcys-induced injury or sclerosis. There are some evidences that GH treatment reverses early atherosclerotic changes in growth hormone deficient adults (Pfeifer et al, 1999) or possess significant cardiac protective effect in uremia rats (Krieg et al, 2008, Rabkin et al, 2008). In addition, GH-releasing peptide ghrelin has recently been reported to protect the endothelium from Hcys-induced injury, which is associated with increases in endothelial nitric oxide synthase expression and reduction of oxidative stress (Hedayati et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that administration of GH may prevent hHcys-induced glomerular injury and therefore the maintenance of normal GH level may be important for the protection of kidneys from hHcys-induced injury or sclerosis. There are some evidences that GH treatment reverses early atherosclerotic changes in growth hormone deficient adults (Pfeifer et al, 1999) or possess significant cardiac protective effect in uremia rats (Krieg et al, 2008, Rabkin et al, 2008). In addition, GH-releasing peptide ghrelin has recently been reported to protect the endothelium from Hcys-induced injury, which is associated with increases in endothelial nitric oxide synthase expression and reduction of oxidative stress (Hedayati et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors of these factors have antifibrotic properties, and ameliorate pathologic changes in the heart in the CRF setting [26], [27]. DPP-4 was previously reported as one of the factors that promotes tissue fibrosis [28]; we have shown that all investigated DPP-4 inhibitors (linagliptin, sitagliptin and alogliptin) decrease plasma concentrations of the fibrosis marker, osteopontin (Table 5), which has recently been called “the killer of patients with CKD” [29], due to its role in vascular calcification.…”
Section: Discussionmentioning
confidence: 99%
“…This protective action of GH on EMT and consequent functional injury in podocytes was found to be due to blockade of the formation of membrane raft platforms with GHR and NADPH oxidase subunits and consequent O 2 .-production. Although there were reports that excessive endogenous production of GH as a peptide hormone secreted by the pituitary gland may be an injurious factor in pathogenesis of some diseases or pathological process such as diabetes mellitus and progressive glomerulosclerosis [24,25], this hormone is often used as a therapeutic agent for different medical conditions, some of which were approved by the U.S. Food and Drug Administration, such as cachexia [26], Turner syndrome [27], chronic renal failure [28], Prader-Willi syndrome [29], and idiopathic short stature (ISS) [30]. In addition to these and other therapeutic uses for improvement of growth in children or adults, GH has also been reported to be used for healing of large burns [31]or in obesity [32], Crohn's disease [33], chronic fatigue syndrome, aging [34] and various degenerative diseases such as Alzheimer's disease [35], multiple sclerosis [36], atherosclerosis [37] and chronic heart failure [38].…”
Section: Discussionmentioning
confidence: 99%
“…It remains unknown whether the application of GH during chronic renal failure could improve renal function and slow the progression of endstage renal disease. In this regard, GH has been reported to possess significant cardiac protective effect in uremia rats [28,40]. Given accumulating evidence that GH has strong antioxidant actions [12,13,[41][42][43], it is possible that its therapeutic application may improve renal damage or glomerular sclerosis associated with local oxidative stress.…”
Section: Discussionmentioning
confidence: 99%